Implications for physical preparation of cadet male table tennis players: analysis of the 2013 asian championship singles final - Glynn, J.; Rusga, T.; Hartley, J.; Mulloy, F.; Moore, J.; Williams, B.; Irwin, G.; Graham-Smith, (ISBS - Conference Proceedings Archive (Konstanz), 2014)
The purpose of this case-study was to attain and describe data on the physical demands placed on elite Asian cadet male table tennis players in high-level competition. The 2013 Asian cadet singles final was notated live while the match was video recorded for further post-analysis. A typical point consisted of 4-5 shots with the player activated for 3.2 s, working for 3.3 s and resting for 17.8 s on average. The frequency of movement types was reported and typical footwork patterns were described for the most common movement types observed (step, linear jump, lateral jump and pivot). Typical footwork sequences were presented for the first two movements when serving and returning. This information could be used to inform a strength and conditioning programme for a developing cadet player seeking to replicate a playing style of an elite Asian cadet player.